2020
DOI: 10.1536/ihj.19-355
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Giant Ascending Aortic Aneurysm with Takayasu Arteritis

Abstract: A 50-year-old man who suffered from dyspnea on effort with hearing loss was referred to our hospital. Computed tomography angiography revealed a giant 90-mm diameter ascending aortic aneurysm with severe calcification and neck vessel occlusion. Transthoracic echocardiography revealed moderate-to-severe aortic regurgitation. His condition was diagnosed as Takayasu arteritis and he underwent aortic valve reimplantation with total arch replacement. Postoperative computed tomography angiography showed complete ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Generally, identification of the aneurysms in the aorta is indication for surgical intervention, so as to leave as little of the lesion as possible in order to avoid the occurrence of postoperative anastomotic dehiscence or pseudoaneurysm [ 11 ]. Kieffer et al reported satisfactory surgical outcome of descending thoracic and thoracoabdominal aortic isolated aneurysm in 33 patients with TAK where except in special cases (e.g., endoaneurysmorrhaphy associated with bypass and endovascular aortic repair), the standard technique for repair of descending thoracic or thoracoabdominal aortic aneurysm was prosthetic endovascular graft replacement [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, identification of the aneurysms in the aorta is indication for surgical intervention, so as to leave as little of the lesion as possible in order to avoid the occurrence of postoperative anastomotic dehiscence or pseudoaneurysm [ 11 ]. Kieffer et al reported satisfactory surgical outcome of descending thoracic and thoracoabdominal aortic isolated aneurysm in 33 patients with TAK where except in special cases (e.g., endoaneurysmorrhaphy associated with bypass and endovascular aortic repair), the standard technique for repair of descending thoracic or thoracoabdominal aortic aneurysm was prosthetic endovascular graft replacement [ 12 ].…”
Section: Discussionmentioning
confidence: 99%